Biodegradable conductive composites of poly(3-hydroxybutyrate) and polyaniline nanofibers: Preparation, characterization and radiolytic effects (eXPRESS Polymer Letters)
Poly(3-hydroxybutyrate) is a biodegradable polyester produced by microorganisms under nutrient limitation conditions. We obtained a biodegradable poly(3-hydroxybutyrate) composite having 8 to 55% of chemically in situ polymerized hydrochloric acid-doped polyaniline nanofibers (70-100 nm in diameter). Fourier transform infrared spectroscopy and X-rays diffractometry data did not show evidence of significant interaction between the two components of the nanocomposite, and polyaniline semiconductivity was preserved in all studied compositions. Gamma-irradiation at 25 kGy absorbed dose on the semiconductive composite presenting 28% of doped polyaniline increased its conductivity from 4.6*10-2 to 1.1 S/m, while slightly decreasing its biodegradability. PANI-HCl biodegradation is negligible when compared to PHB biodegradability in an 80 day timeframe. Thus, this unprecedented all-polymer nanocomposite presents, at the same time, semiconductivity and biodegradability and was proven to maintain these properties after gamma irradiation. This new material has many potential applications in biological science, engineering, and medicine.